Pengaruh Extender Tahu pada Sosis Daging Sapi Ditinjau dari Kualitas Kimia: Beef, Sausage, Tofu Extender - Dian Ratnasari; Roisu Eny Mudawaroch; Zulfanita Zulfanita (Jurnal Riset Agribisnis dan Peternakan, 2021)
Making beef sausage requires additional ingredients for making sausages called extenders. The use of extender material is needed as a binder that is able to provide different chemical qualities. This study aims to determine the effect of tofu extender substitution on beef sausage in terms of chemical quality. The treatments in this study were tofu substitution in meat of 0%, 0.2%, 0.4%, 0.6% and 0m8%. The research design used a completely randomized design (CRD), with 5 treatments and 4 replications. The results showed that the addition of tofu extenders showed significant differences in fat content in beef sausages. Treatment T0 with treatment T1, T2, T3, and T4. The addition of tofu extenders showed significant differences in protein content in beef sausages. The protein content of beef sausage with treatment T0 was significantly different from treatment T1, T2, T3, and T4. The addition of a tofu extender showed a significant difference in the water content of beef sausage. The water content of beef sausage with treatment T0 was significantly different from treatment T1, T2, T3, and T4. The addition of tofu extenders significantly reduced the protein content and fat content of sausages. The water content decreased significantly in the sausage that was added to the tofu extender.